Exploring adults as support persons for improved pre-exposure prophylaxis for HIV use among select adolescents and young adults in the Deep South. - Samantha V Hill; Jarvis Johnson; Fazlur Rahman; Emily F Dauria; Michael Mugavero; Lynn T Matthews; Tina Simpson; Latesha Elopre (PLoS ONE)
Purpose Pre-exposure prophylaxis for HIV (PrEP) is an effective yet underutilized biomedical tool for adolescents and young adults' (AYA) HIV prevention due to barriers such as PrEP adherence. We assessed HIV prevention knowledge, attitudes and beliefs from adults who self-identified as a primary support person to an AYA. Methods We surveyed AYA primary support persons at an academic hospital. Univariate and multivariate regression analyses were completed to identify factors associated with the belief AYAs engaging in HIV-associated behaviors should use PrEP and willingness to support AYAs on PrEP. Results 200 primary support persons completed the survey. Participants were predominately female (77%) and black (56%). Nearly all primary support persons believed AYAs engaging in HIV-associated behaviors should take PrEP (94%) and 98% would support an AYA taking PrEP via transportation to appointments, assistance with refilling prescriptions, medication reminders, or encouragement. Conclusions Primary support persons are willing to support AYAs using PrEP.